ADAM10: Possible functions in enamel development - Shahid, Shifa; Ikeda, Atsushi; Layana, Michelle C.; Bartlett, John D. (Frontiers in Physiology, 2022)
AADAM10 is A Disintegrin And Metalloproteinase (ADAM) family member that is membrane bound with its catalytic domain present on the cell surface. It is a sheddase that cleaves anchored cell surface proteins to shed them from the cell surface. ADAM10 can cleave at least a hundred different proteins and is expressed in most tissues of the body. ADAM10 is best characterized for its role in Notch signaling. Interestingly, ADAM10 is transported to specific sites on the cell surface by six different tetraspanins. Although the mechanism is not clear, tetraspanins can regulate ADAM10 substrate specificity, which likely contributes to the diversity of ADAM10 substrates. In developing mouse teeth, ADAM10 is expressed in the stem cell niche and subsequently in pre-ameloblasts and then secretory stage ameloblasts. However, once ameloblasts begin transitioning into the maturation stage, ADAM10 expression abruptly ceases. This is exactly when ameloblasts stop their movement that extends enamel crystallites and when the enamel layer reaches its full thickness. ADAM10 may play an important role in enamel development. ADAM10 can cleave cadherins and other cell-cell junctions at specific sites where the tetraspanins have transported it and this may promote cell movement. ADAM10 can also cleave the transmembrane proteins COL17A1 and RELT. When either COL17A1 or RELT are mutated, malformed enamel may occur in humans and mice. So, ADAM10 may also regulate these proteins that are necessary for proper enamel development. This mini review will highlight ADAM10 function, how that function is regulated by tetraspanins, and how ADAM10 may promote enamel formation.